Sustainable Practices and Company Performance in Restaurant Business at PT XYZ: The Moderating Role Of Supply Chain Visibility - Irwan Darmawan; Aman Wirakartakusumah (Keynesia : International Journal of Economy and Business, 2023)
The study was conducted to see the effect of sustainable practices and company performance on the restaurant business at PT XYZ: the moderating role of supply chain visibility. The population of this study is managerial level employees who work in PT XYZ restaurants located in Jabodetabek. Furthermore, the sample approach used is non-probability sampling, with the sampling strategy used in this study is purposive sampling. In this study, the minimum sample size used was 102 respondents. Then the method used in this research is the Partial Least Square (PLS) approach in Structural Equation Modeling (SEM). The results showed that sustainable procurement practices have a positive and significant effect on company performance. Then sustainable manufacturing practices have a positive and significant effect on company performance. Furthermore, supply chain visibility cannot moderate sustainable procurement and sustainable manufacturing on company performance in the restaurant business.